Characterization of the interface of co‐extruded asymmetric aluminum‐titanium composite profiles. Issue 12 (December 2014) - Grittner, N.; Striewe, B.; von Hehl, A.; Engelhardt, M.; Klose, C.; Nürnberger, F.; von Hehl, Axel; Weise, Jörg
<x xml:space="preserve">Abstract</x> The combination of different light alloys enables lightweight solutions with tailor‐made properties at the macroscopic global as well as at the microscopic scale. In this context co‐extrusion by a lateral angular co‐extrusion (LACE) process offers a great potential for advanced profiled structures. While titanium alloys show particular high mechanical strength and good corrosion resistance, aluminium alloys provide a considerable high specific bending stiffness along with low materials costs. The mechanical properties of metallic compounds strongly depend on the bonding mechanisms, which are initiated during processing. In order to enable a rigid adhesive bond between Al and Ti in this study the extrusions were processed by means of a newly developed lateral angular co‐extrusion that is a modified equal channel angular pressing process (ECAP). Latter is known for promoting diffusion bonding by reducing the activation energy. Hence, the study is focused on the general manufacturing of Al–Ti‐compounds by lateral angular co‐extrusion. The second aim of the study was to investigate the development of the bonding zone during processing. Experiments were made with the material combination Al99.5 and titanium grade 2. The bonding zones of the co‐extruded samples were analyzed by scanning electron microscopy and energy dispersive X‐ray analysis. The bond strength was determined by quasi‐static tensile tests. Compared to the as‐extruded condition an intermetallic layer was formed during heat treatment. The layer was characterized by scanning electron microscopy and electron probe micro analysis.